Pengaruh Ukuran Perusahaan, Struktur Modal, dan Likuiditas terhadap Nilai Perusahaan - indiraswari, susmita dian (Department of Accounting, Faculty of Economics & Business, 2024)
This research aims to determine the influence of company size, capital structure, and liquidity on firm value. This quantitative and verificative study uses an associative design. The population consists of mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, totaling 40 companies. The sample was selected using purposive sampling, resulting in 14 companies. Data was collected through documentation (financial statements of the companies) accessed from http://www.idx.co.id. The data was analyzed using multiple linear regression analysis. The results of this study conclude that: Company size, capital structure, and liquidity have a significant simultaneous effect on the value of mining companies. Company size does not have a significant effect on the value of mining companies. Capital structure has a significant effect on the value of mining companies. Liquidity has a significant effect on the value of mining companies.